2006
DOI: 10.1097/01.phm.0000184153.98344.a4
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects and Complications After Percutaneous Disc Decompression Using Coblation Technology

Abstract: Based on this preliminary data, nucleoplasty seems to be associated with short-term increased pain at the needle insertion site and increased preprocedure back pain and tingling numbness but without other side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 51 publications
1
46
0
1
Order By: Relevance
“…Gerszten et al described no nerve root injuries in a series of 67 patients [12] whereas Bhagia et al observed new numbness and tingling in 26% and new areas of back pain in 15% of 53 patients [13] which, from our point of view, hint at nerve root damage. However, it can be assumed that some patients encounter damage to the nerve root during nucleoplasty.…”
Section: Introductionmentioning
confidence: 82%
“…Gerszten et al described no nerve root injuries in a series of 67 patients [12] whereas Bhagia et al observed new numbness and tingling in 26% and new areas of back pain in 15% of 53 patients [13] which, from our point of view, hint at nerve root damage. However, it can be assumed that some patients encounter damage to the nerve root during nucleoplasty.…”
Section: Introductionmentioning
confidence: 82%
“…Sporadic cases of thermal injury to the cauda equina, disc herniation, and osteonecrosis of the vertebral endplates following IDET and nucleoplasty have been reported1,12,21). Transient nerve injury appears to be the most common complication after these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complications reported by Bhagia et al 19 at the procedure after 24 hours in 49 patients were: soreness at the needle insertion site in 76%; new numbness in 26%; increased intensity of pre-procedure back pain in 15% and new areas of back pain in 15% of the patients. At two weeks post-procedure, no patient had soreness at the needle insertion site nor new areas of back pain, but new numbness was present in 15% of the patients.…”
Section: Discussionmentioning
confidence: 99%